Cuba y Francia: Transparencias fugaces de un desencuentro (1808-1814) - Katia Figueredo Cabrera (Caravelle)
This paper analyzes the poetic corpus generated in Cuba during the Napoleonic occupation of Spain. Selected poems do not represent a whole, but within the levels shown are an obvious sign of growing diversity metrics in its various manifestations, as well as Francophobia fueled by the emotional charge "patriotic" and the creative will of the residents poets in the largest of the Antilles.